Acessibilidade em trabalhos acadêmicos para surdos sinalizantes: E-book acessível - Thomazini, Eduardo (Universidade Federal de São Carlos, 2024)
Deafness is a disability marked by the total or partial absence of hearing. Deaf people face challenges mainly related to people's attitudes and lack of adaptations. These people mostly use the Brazilian Sign Language (LIBRAS) as a legal means of communication and expression. The presence of this language contributes to reducing the difficulties faced. LIBRAS is a means of communication that uses signs to exchange information and is the language mostly used by the deaf community. Therefore, the present work aims to: Create an accessible e-book for deaf people, based on a summary of scientific works. In pursuit of this objective, QR Codes were used to store YouTube video links containing summaries of previously selected academic works, with interpretation in LIBRAS. The QR Codes used are more modern barcodes, capable of storing more information than their predecessors, offering a wide range of usage possibilities. To develop the e-book, support from the NEPEDE-EES study group was necessary, due to the large number of scientific work results, as well as the partnership with the extension project (ProEx-UFSCar) which was funded by a LIBRAS interpreter to produce accessible videos. Using qualitative research and the UFSCar Academic Works Repository website, inclusion and exclusion criteria were established for the selection of works to be interpreted. This analysis revealed that only a small fraction of researchers at the University have carried out research related to Special Education, an essential topic for the development of new technologies, in addition to being fundamental to providing the inclusion and autonomy of people with disabilities. Because of this, there still needs to be greater publicity and encouragement for this type of research.
Accessibility in academic work for deaf signers: Accessible e-book
Keywords: Educação especial; Acessibilidade; Tecnologia assitiva; Surdez; Libras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO